![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\frac{1}{2018}+\frac{2}{2017}+...+\frac{2017}{2}+2018\)
\(=\left(\frac{1}{2018}+1\right)+\left(1+\frac{2}{2017}\right)+...+\left(\frac{2017}{2}+1\right)+1\)(2018 số hạng 1)
\(=\frac{2019}{2018}+\frac{2019}{2017}+...+\frac{2019}{2}+\frac{2019}{2019}=2019\left(\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2019}\right)\)
Mà \(B=\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+...+\frac{1}{2019}\)
=> Khi đó : \(\frac{A}{B}=\frac{2019\left(\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2019}\right)}{\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2019}}=2019\)
??????????????????????????????????????????????????????????????????????????????????????????????????????????????
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2A=2+2^2+2^3+2^4+...+2^{2017}\)
\(A=2A-A=2^{2017}-1\)
=> A<B
![](https://rs.olm.vn/images/avt/0.png?1311)
999 - 888 - 111 + 111 - 111 + 111 - 111
= 111 - 111 + 111 - 111 + 111 - 111
= 0 + 111 - 111 + 111 - 111
= 111 - 111 + 111 - 111
= 0 + 111 - 111
= 111 - 111
= 0
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{B}{A}=\frac{\frac{2016}{1}+\frac{2015}{2}+...+\frac{2}{2015}+\frac{1}{2016}}{\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+..+\frac{1}{2016}+\frac{1}{2017}}\)
\(\frac{B}{A}=\frac{\left(\frac{2016}{1}+1\right)+\left(\frac{2015}{2}+1\right)+...+\left(\frac{1}{2016}+1\right)}{\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2016}+\frac{1}{2017}}\)
\(\frac{B}{A}=\frac{\frac{2017}{1}+\frac{2017}{2}+...+\frac{2017}{2016}}{\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2016}+\frac{1}{2017}}\)
\(\frac{B}{A}=\frac{2017\cdot\left(\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2016}\right)}{\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2016}+\frac{1}{2017}}=2017\div\frac{1}{2017}=4068289\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Có 2A = 2-2^2+2^3-2^4+.....+2^1015-2^2016+2^2017
3A = 2A+A = (2-2^2+2^3-2^4+....+2^2015-2^2016+2^2017) + (1-2+2^2-2^3+....+2^2016)
= 2^2017 + 1
=> 3A - 2^2017 = 2^2017 + 1 - 2^2017 = 1